Selective Sentinel Lymph Node Dissection in Lower Extremity Melanoma. Issue 3 (March 2016) - Miranda, Suzette G.; Parrett, Brian M.; Li, Rui (Rachel); Lee, Grant; Chang, Tiffany; Fadaki, Niloofar; Cardona-Huerta, Servando; Cleaver, James E.; Kashani-Sabet, Mohammed; Leong, Stanley P.
Abstract : Background: There is debate as to whether deep inguinal lymph nodes should be removed with the superficial or femoral lymph nodes during sentinel lymph node biopsy for lower extremity melanoma, when both superficial and deep inguinal lymph nodes are identified by preoperative lymphoscintigraphy. This study evaluated the lymphatic drainage patterns in lower extremity melanoma to determine whether certain patterns could be used to limit the level of node removal and define the extent of dissection. Methods: A retrospective outcomes review was performed of lower extremity melanoma patients with excision and sentinel lymph node biopsy from 1995 to 2010. Outcomes included location of sentinel lymph node drainage basins, sentinel lymph node–positivity, and disease-free and overall survival, with drainage patterns compared between above- and below-knee melanomas. Results: Of 499 patients with lower extremity melanoma having sentinel lymph node biopsy, 356 had below-the-knee and 143 had above-the-knee melanoma. For below-knee melanoma, the node-positivity rate was 23 percent for superficial inguinal, 0 percent for deep inguinal, and 50 percent for popliteal basins. For above-knee melanoma, the positivity rate was 21 percent for superficial inguinal, 33 percent for deep inguinal basins, and 0 percent for popliteal basins. Importantly, no patients with a negative superficial inguinal sentinel lymph node had a positive deep inguinal sentinel lymph node on final pathologic evaluation. Conclusions: A difference was noted in patterns of sentinel lymph node drainage from lower extremity melanoma below and above the knee. Biopsy for deep inguinal basins may be deferred if there is simultaneous drainage to the superficial inguinal basin by preoperative lymphoscintigraphy. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, II.